Normal congruences with focal bicylindrical surfaces - Koneva, N. P. (Ukrains’kyi Matematychnyi Zhurnal, 1993)
A system of equations determining normal con uences with focal surfaces (bicylinders) is found in a biaxial space of hyperbolic type by using a moving frame of the space and the method of Cartan exterior forms. The geometric construction of these congruences is presented.